Studies on some blood and body fluid characteristics in zebu and European breeds of cattle in the hot humid tropics of Nigeria - Olusanya, S.K. (1979)
Three breeds of cattle, the White Fulani (zebu breed), German Brown and Holstein (European breeds), of the same age, kept under identical conditions were studied to delineate differences in some body fluid charateristics. Data on comparative values of blood contituents, serum constituents and body fluid volumes are included. The zebu breed had different values from the European breed in the following parameters: PCV, Hb, RBC, TBW, plasma volume and erythrocyte potassium.